2020
DOI: 10.1007/s10096-020-03828-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of two rapid molecular test systems to establish an algorithm for fast identification of bacterial pathogens from positive blood cultures

Abstract: Fast identification of pathogens directly from positive blood cultures is of highest importance to supply an adequate therapy of bloodstream infections (BSI). There are several platforms providing molecular-based identification, detection of antimicrobial resistance genes, or even a full antimicrobial susceptibility testing (AST). Two of such test systems allowing rapid diagnostics were assessed in this study: The Biofire FilmArray® and the Genmark ePlex®, both fully automated test system with a minimum of han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
(41 reference statements)
4
15
2
Order By: Relevance
“…Identification to the species level was obtained for 61% of GP bacteria, 90% of GN bacteria, and 87.5% of fungi. Identification to the genus level increased detection rate of GN pathogens to 93%, while 87 and 88% had been previously detected in other studies analyzing 125 and 33 positive blood cultures respectively (Huang et al, 2019;Oberhettinger et al, 2020). Identification to the genus level increased identification rate to 91% for the GP strains, mainly because putative contaminants such as Coagulase-negative Staphylococcus species, Corynebacterium and Micrococcus strains are only identified to the genus level, with the exception of S. epidermidis and S. lugdunensis species identified by the BCID-GP Panel.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Identification to the species level was obtained for 61% of GP bacteria, 90% of GN bacteria, and 87.5% of fungi. Identification to the genus level increased detection rate of GN pathogens to 93%, while 87 and 88% had been previously detected in other studies analyzing 125 and 33 positive blood cultures respectively (Huang et al, 2019;Oberhettinger et al, 2020). Identification to the genus level increased identification rate to 91% for the GP strains, mainly because putative contaminants such as Coagulase-negative Staphylococcus species, Corynebacterium and Micrococcus strains are only identified to the genus level, with the exception of S. epidermidis and S. lugdunensis species identified by the BCID-GP Panel.…”
Section: Discussionmentioning
confidence: 68%
“…Gram stain is required prior to performing the test to choose the appropriate ePlex BCID Panel(s) and prevents the user from running the test on false-positive blood cultures. The list of targets present on the panels seems well designed, as only 9% of GP bacteria, 5% of GN bacteria, and 13% of fungi were not included on the panels in our study, while previous reports found between 2.2% (for the BCID-GP Panel only) and 6% of pathogens untargeted by the panels (Maubon et al, 2018;Huang et al, 2019;Carroll et al, 2020;Oberhettinger et al, 2020). Identification to the species level was obtained for 61% of GP bacteria, 90% of GN bacteria, and 87.5% of fungi.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations